(untitled) (Research, Society and Development, 2020)
Objective: to carry out an integrative review on the role of prebiotics and probiotics in maintaining health, as well as their applications in the treatment of chronic idiopathic constipation (CIC), irritable bowel syndrome (IBS) and inflammatory bowel disease (IBD). Methodology: this is an integrative literature review, whose search for studies was carried out in the Cochrane and PubMed databases, with analysis of studies published in the last ten years (2010-2020) written in English. Results: The use of probiotics in CIC and IBS has shown beneficial effects in reducing the symptoms of these diseases, modifying the microbiota and improving the quality of life of patients. In CIC, inulin was the prebiotic with the most positive effects on the symptoms of the disease. In IBD, the use of prebiotics and probiotics showed slightly greater beneficial effects for UC than for CD. Conclusion: Prebiotics and probiotics can bring both preventive and therapeutic benefits to intestinal health, with direct and indirect actions on the microbiota, immunity and metabolic processes of the host. The use of these compounds and microorganisms in the studied diseases show promising results, mainly in the field of probiotics. From the analysis of clinical trials, the promising strains in the treatment of IBD were Bifidobacterium, Lactobacillus, Enterococcus faecium (DC and RCU) and Clostridium butyricum (RCU). However, we emphasize the need for more homogeneous studies in the treatment of CD with probiotics and prebiotics and the use of prebiotics in IBS.